Strategic development of property auctions market in Malaysia - Wong, W.C.; Lee, J.Y.M.; Daud, M.N.; Ng, P.L.; Chan, W.S. (American Real Estate Society, 2014)
Despite its existence in the property market scene for over a century, little is known about the property auction market in Malaysia. We analyze the types, size, occurrence, and performance of property auctions in Malaysia. In comparison to mature markets such as Australia and New Zealand, the auction market in Malaysia is relatively small (0.03% of total property sales) and dominated by distress or foreclosure sales. Outdated laws coupled with an unregulated auction environment have generated myriad challenges among which are the presence of syndicates (dummy bidders) and negative stigma associated with auctions. We highlight initiatives that could be taken by policymakers to revitalize the property auction market in Malaysia.